Transformation of Islamic Religious Education through Internalization of Religious Moderation for Deradicalization of Students in Schools - Nabil Tito Prasetyo; Muhammad Fajar; Nur Hasanah; Sela Sopiana; Idham kholid; Mujib Mujib; Sovia Mas Ayu (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the transformation of Islamic Religious Education (PAI) through the internalization of religious moderation values as a strategic effort in deradicalizing students within the school environment. Religious moderation is understood as an important approach in shaping religious attitudes that are tolerant, inclusive, and balanced amid the challenges of globalization and the development of information technology. The research method used is a qualitative approach with a library research design, drawing from relevant books, scholarly journals, and educational policy documents. Data analysis was conducted using content analysis to identify, examine, and interpret the concept of religious moderation in the context of Islamic education. The findings indicate that the internalization of religious moderation values in PAI learning can be implemented through curriculum integration, exemplary behavior of educators, habituation of tolerant attitudes in schools, and strengthening contextual religious literacy. These strategies contribute to forming students with moderate, critical thinking, and resilience against radical ideologies. Thus, the transformation of Islamic Religious Education based on religious moderation plays a strategic role in creating a peaceful, inclusive educational environment and strengthening national character.